Antiproliferative and apoptotic activity of crude skin secretion from Malaysian Toad (Bufo asper) on in vitro colorectal cancer cells - Saad Sabbar Dahhama, Muhammad Asifa, Yasser M Tabanaa , Doblin Sandaib, Amin Malik Shah Abdul Majida, Gam Lay Harna (Journal of Applied Pharmaceutical Science, 2017)
Earlier, a protein profile of Bufo asper skin secretion had been identified. The crud skin extract possessed antimicrobial activity against wide range of pathogenic bacteria. In the present communication, the antiproliferative and apoptogenic properties of toad’s skin secretion (TSS) have been evaluated in colorectal cancer cell line. The antiproliferative activity of TSS was tested over HCT 116 and CCD-18Co cells by 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT )assay. Hoechst and rhodamine staining and caspases 3 and 7 were evaluated in order to verify cell death and apoptosis. TSS exhibited potent dose-dependent cytotoxic effect against human colorectal cancer cell line HCT 116 cells with an IC50 (15± 1.19 μg/mL). Conversely, the viability of normal colonic fibroblasts cell line CCD-18Co was much less affected by similar doses of TSS. Morphological studies by microscope on HCT 116 cells indicated certain events of apoptosis such as nuclear shrinkage, membrane blebbing and vacuolization of cells. This was further supported by activation of caspases 3 and 7. Considering the growing interest of developing naturally occurring host-defense peptides for new anticancer agents, data presented in this work strongly reinforce the validity of Bufo asper skin secretion as a rich source of new anticancer compounds.
Keywords: Bufo asper, apoptotic, anticancer, colorectal cancer.